2D modeling of turbulence wave number spectra reconstruction from radial correlation reflectometry data. (18th June 2015) - Gusakov, E Z; Irzak, M A; Popov, A Yu; Teplova, N V
Abstract: Computational analysis of radial correlation reflectometry in the framework of a model accounting for 2D probing wave propagation and scattering is performed. The procedure of the turbulence wavenumber spectra reconstruction from radial correlation reflectometry data previously proposed in the case of normal incidence of probing wave onto the 1D plasma is justified for the real geometry of a reflectometry experiment at large and modest scale fusion plasmas.